Políticas lingüísticas sensibles al género y la deconstrucción de estereotipos de género en los manuales de ELE - Kuzmanović Jovanović, Ana (Verba hispanica, 2015)
This paper examines the impact of gender representations in Spanish/L2 textbooks on perpetuation or deconstruction of gender stereotypes in the classroom. Although the results of numerous studies of gender representation in such books performed in the past two decades suggest that teaching materials have been an important instrument in perpetuating gender stereotypes, recent researches have revealed certain changes in this area. The present analysis supports these findings. The research corpus consists of eleven textbooks of Spanish/L2 (level A1 and A2) by different Spanish publishers, all of them published in the last four years. The gender roles in which women and men appear are critically analyzed. The results of the analysis suggest that there has been a conscious effort by both authors and editors in order to change the stereotypical gender representation in these didactic materials. We offer an explanation for these changes suggesting that they can be accounted for by the action of a different model of gender sensitive language policies, the bottom-up model, where the crucial factors of change are not the activities of the official institutions but rather are to be found in different communities of practice, i.e., all people involved in creating, publishing and distributing teaching materials, as well as linguists who investigate the relationship between language and gender.
Keywords: Spanish; španščina; jezikovni učbeniki; gramatika spolov; ideologija spolov; jezikovna politika